Enhancing Children's Speaking Skills through Pop-Up Book Media: A Classroom Action Research: Meningkatkan Kemampuan Berbicara Anak melalui Media Buku Pop-Up: Penelitian Tindakan Kelas - Maghfiroh, Yeni; Wahyuni, Akhtim (Universitas Muhammadiyah Sidoarjo, 2023)
This study aimed to improve the speaking skills of children by utilizing Pop-Up book media, preceded by developing their listening skills. Conducted at Dharma Wanita Persatuan Pucang Kindergarten, the research employed Classroom Action Research methodology. The pre-cycle results revealed a 51.4% average score for children's speaking ability. However, after implementing the Pop-Up book media in the first cycle, the percentage increased significantly to 68.5%, showing a 12.9% improvement from the maximum score. The researcher continued to apply action in cycle II, leading to a remarkable rise in the average score to 85.3%, signifying an overall enhancement of 28.9% from cycles I and II. The results demonstrate that employing Pop-Up book media effectively enhances children's speaking skills, carrying implications for language skill development in early childhood education. Highlights: The use of Pop-Up book media: The study focuses on utilizing Pop-Up book media to enhance children's speaking skills, providing an engaging and interactive learning approach. Classroom Action Research: The research methodology employed is Classroom Action Research, enabling a systematic investigation of the effectiveness of the intervention. Language development in early childhood: The study highlights the importance of language skill development during early childhood education, emphasizing its implications for lifelong language proficiency. Keywords: Speaking skills, Pop-Up book media, Classroom Action Research, Children, Language development.